A Quality by Design Approach in Pharmaceutical Development of Non-Viral Vectors with a Focus on miRNA - Ioana Toma; Alina Silvia Porfire; Lucia Ruxandra Tefas; Ioana Berindan-Neagoe; Ioan Tomuță (MDPI AG, 2022)
Cancer is the leading cause of death worldwide. Tumors consist of heterogeneous cell populations that have different biological properties. While conventional cancer therapy such as chemotherapy, radiotherapy, and surgery does not target cancer cells specifically, gene therapy is attracting increasing attention as an alternative capable of overcoming these limitations. With the advent of gene therapy, there is increasing interest in developing non-viral vectors for genetic material delivery in cancer therapy. Nanosystems, both organic and inorganic, are the most common non-viral vectors used in gene therapy. The most used organic vectors are polymeric and lipid-based delivery systems. These nanostructures are designed to bind and protect the genetic material, leading to high efficiency, prolonged gene expression, and low toxicity. Quality by Design (QbD) is a step-by-step approach that investigates all the factors that may affect the quality of the final product, leading to efficient pharmaceutical development. This paper aims to provide a new perspective regarding the use of the QbD approach for improving the quality of non-viral vectors for genetic material delivery and their application in cancer therapy.